Clinical Characteristics and Mortality Risk Factors of Hospitalized COVID-19 in Children: An Experience of Two Years Pandemic in Regional Referral Hospital - Rabbani, Gefaritza; Putra, David Anggara; Andarini, Ismiranti (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Coronavirus disease 2019 (COVID-19) has spread worldwide rapidly. COVID-19 in children is relatively mild compared to adults. However, several studies showed high mortality rates in children with underlying diseases. This study aimed to describe the clinical characteristics and outcomes of pediatric COVID-19 cases in regional referral hospital. This study was retrospective observational study using data from Medical Record Dr. Moewardi General Hospital between October 1st, 2020 and October 30th, 2022. The epidemiological and clinical data were extracted from the database and were compared with outcomes of patients. All statistical analyses were performed by SPSS software version 27. This study enrolled 371 (19,9%) children with confirmed RT-PCR SARS CoV-2 from 1856 hospitalized suspected children whereas 55% were males, and 63% aged under 5 years old. Moderate-severe patients accounted for 18% of the cases. Cough (74,4%), fever (66,6%) and shortness of breath (22,6) are the most common symptoms while 99 (26,7%) patients who had chronic diseases with the most common diseases being congenital heart disease, hematological malignancy and neurological disorders. Patient outcomes were significantly related to age, degree of severity and chronic disease with p=0.004, p< 0.001, and p< 0.001 respectively. After performing multivariate regression analysis, degree of severity [p<0.001; adjusted OR = 28.03, 95% CI (10.73–73.21)] was found to be significant predictors for mortality. The clinical and epidemiological data revealed that the majority symptom were cough, fever and shortness of breath. Mortality rate during hospitalization was higher in children with moderate-to-severe COVID-19.